Creating narrative games with Unity : build a complete narrative game from start to finish using the Unity game engine - Manning, Jon (O'Reilly, 2016)
"The course takes you through the complete process of building a narrative game using nothing but Unity, some open source dialogue software, some free art and music from open source locations, and your own smarts. The course works best for those with a very basic understanding of the Unity game engine interface and C# programming."--Resource description page.